Financial engineering and arbitrage in the financial markets - Dubil, Robert (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley, 2011)
A whole is worth the sum of its parts. Even the most complex structured bond, credit arbitrage strategy or hedge trade can be broken down into its component parts, and if we understand the elemental components, we can then value the whole as the sum of its parts. We can quantify the risk that is hedged and the risk that is left as the residual exposure. If we learn to view all financial trades and securities as engineered packages of building blocks, then we can analyze in which structures some parts may be cheap and some may be rich. It is this relative value arbitrage principle that drives a.
Financial Engineering and Arbitragein the Financial Markets; Contents; Introduction; 1 Purpose and Structure of Financial Markets; 1.1 Overview of Financial Markets; 1.2 Risk Sharing; 1.3 Transactional Structure of Financial Markets; 1.4 Arbitrage: Pure Versus Relative Value; 1.5 Financial Institutions: Transforming Intermediaries vs Broker-Dealers; 1.6 Primary (Issuance) and Secondary (Resale) Markets; 1.7 Market Players: Hedgers vs Speculators; 1.8 Preview of the Book; PART I RELATIVE VALUE BUILDING BLOCKS; 2 Spot Markets; 2.1 Bonds and Annual Bond Math; 2.1.1 Zero-Coupon Bond.
Includes bibliographical references and index.
Print version record.
Keywords: Financial engineering; Arbitrage; Capital market; Investments -- Mathematics; Arbitrage; Capital market; Financial engineering; Investments -- Mathematics; BUSINESS & ECONOMICS -- Finance; Arbitrage; Capital market; Financial engineering; Investments -- Mathematics; Electronic books